Potential Local Wisdom of Sajang Village and Efforts to Conserve Yards as an Effort to Develop Agro-Tourism - Rosalina Edy Swandayani; Meilinda Pahriana Sulastri (Jurnal Penelitian Pendidikan IPA, 2025)
Sajang Village, located near Mount Rinjani National Park in West Nusa Tenggara, has significant potential for agro-tourism due to its biodiversity, traditional culture, and unique yard-based agricultural landscapes. Despite this potential, previous initiatives have overlooked the critical role of tourist perceptions and the conservation of home yards in shaping effective agrotourism strategies. This research aims to incorporate tourist preferences and yard conservation into the sustainable development of agro-tourism in Sajang Village. This descriptive qualitative study, conducted in June–July 2025, surveyed tourists and used SWOT analysis to evaluate the village’s strengths, weaknesses, opportunities, and threats. Findings reveal that 54.7% of tourists consider yard plant diverse, 24.6% rate it as very diverse, and 20.7% as quite diverse. Fruit and vegetable plants dominate the yards (86.7%), with ornamental plants comprising 13.3%. All surveyed tourists supported developing Sajang Village for agro-tourism, valuing its natural diversity, authentic experiences, and traditional use of home yards for ornamental, vegetable, and spice plants. The research underscores the importance of diversifying tourism activities such as fruit picking, coffee plantation tours, and local product promotion alongside conservation measures that prioritize native species and maintain traditional yard layouts. Collaboration among communities, authorities, and stakeholders is crucial for infrastructure and effective promotion. Integrating visitor perspectives with yard conservation offers a replicable model for sustainable agro-tourism, strengthening both local livelihoods and environmental stewardship.